2023
DOI: 10.3389/fpsyg.2022.1052713
|View full text |Cite
|
Sign up to set email alerts
|

Prosociality and health: Identification with all humanity is a replicable predictor of prosocial motivation for health behaviors

Abstract: The acute phase of the COVID-19 pandemic may have passed, but the pandemic remains a major worldwide health concern that demands continued vigilance. Are there individual differences that predict the motivation to continue to wear masks and to create physical distance in public? Previous research conducted early in the pandemic had suggested that a particular social identity—identification with all humanity—is one underlying factor that contributes to people’s cooperation with health behavior guidelines. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 73 publications
3
3
0
Order By: Relevance
“…The study also replicated previous findings (e.g., Barragan et al, 2021 Barragan & Meltzoff, 2023; Wang et al, 2023) about the predictive power of IWAH on compliance with COVID-19 health guidelines, and other research on the relationship between global identification and global cooperation (e.g., Buchan et al, 2011) with a measure specifically about pandemic preparedness.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The study also replicated previous findings (e.g., Barragan et al, 2021 Barragan & Meltzoff, 2023; Wang et al, 2023) about the predictive power of IWAH on compliance with COVID-19 health guidelines, and other research on the relationship between global identification and global cooperation (e.g., Buchan et al, 2011) with a measure specifically about pandemic preparedness.…”
Section: Discussionsupporting
confidence: 85%
“…The study also replicated previous findings (e.g., Barragan et al, 2021Barragan & Meltzoff, 2023Wang et al, 2023) about the predictive power…”
Section: Asupporting
confidence: 89%
See 1 more Smart Citation
“…Work that moves beyond thinking about families from a dyadic perspective to capturing triadic, family, and multilevel (e.g., individual × family effects) shared assets and experiences is warranted. Further work focusing on other kin relationships such as grandparents (Cortes Barragan et al, 2023; Gonzalez & Barnett, 2023), godparents, and fictive kin, and integrating more diverse definitions of families is critical. Second, all the studies focused on family relationships in the context of cisgender, heterosexual families.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of health worries matters and extends beyond one's health. A study conducted by Barragan and Meltzoff revealed that certain people have a strong desire to look out for the health of strangers, which is strongly correlated with their concern for all of humanity rather than just their own community or nation ( 58 ). Our data also supported H5 and indicated that individuals with higher health worries are more likely to follow COVID-19 good practices.…”
Section: Discussionmentioning
confidence: 99%